BLOCKCHAIN IMPLEMENTATION TRENDS IN DIGITAL ARCHIVES: BIBLIOMETRIC ANALYSIS - Narudhu, Anum Arum; Palupi, Indah Widdi; Sofiyani, Zulfatun (Pustabiblia: Journal of Library and Information Science, 2024)
The increasing development of digital archives requires an optimal solution to face challenges in its security aspects. These challenges can be overcome by using blockchain as an encryption that keeps the archive reliable and trustworthy. This study aims to determine the development of scientific article publications that identify the relationship between blockchain and archives. Data was obtained from the database published by Web of Science (WoS) from 2015-2023. The keywords used to obtain appropriate results are “Blockchain” and “Archive” based on topics. Then 106 documents were obtained, namely articles and proceedings papers. The search results were exported in BibTex format and analyzed bibliometrically using the biblioshiny web interface from R Studio software. The results of the analysis show that blockchain-related publications in digital archives are still not very developed. This is because publications have only started since 2015, which is the beginning of innovation in the application of blockchain in digital archives. In addition, it is supported by treemap and wordcloud analysis which did not find the word archive.